Application of cadmium prediction models for rice and maize in the safe utilization of farmland associated with tin mining in Hezhou, Guangxi, China. (15th September 2021) - Yang, Yeyu; Li, Cheng; Yang, Zhongfang; Yu, Tao; Jiang, Hongyu; Han, Min; Liu, Xu; Wang, Jue; Zhang, Qizuan
Abstract: Cadmium (Cd) contamination in soil and crops caused by mining activities has become a prevalent concern in the world. Given that different crops have varying Cd bioaccumulation factors, crops with low Cd bioaccumulation abilities can be selected for the safe usage of Cd -contaminated lands. This study aimed to investigate Cd contamination in soil and crops and the influencing factors of soil Cd activity in a tin mining area (TMA) and control area (CA) and to put forward suggestions for the safe usage of farmlands by developing prediction models of Cd content in different crop grains. We collected 72 and 40 pairs of rice and maize grain samples, respectively, along with their rhizosphere soil samples and 6176 topsoil samples. The results showed that compared with the CA, the Cd pollution was more severe in the cultivated soil and crop grains around TMA. Furthermore, rice has a strong ability to transport Cd from soil to grains, whereas maize has a poor Cd uptake ability. The total organic carbon, CaO, pH, and Mn in soil play key roles in the transfer of Cd from soil to crop grains. Using these parameters and Cd concentration in soil, two sets of accurate Cd prediction models were developed for maize and rice. Based on the Cd concentration in the topsoil and predicted Cd concentration in crop grains, the safe utilization scheme of farmland was proposed. The proportions of priority protection, safe exploitation, planting adjustment, and strict control were 72.59%, 22.77%, 3.16%, and 1.48% in the TMA, respectively. The values reached 80.51% (priority protection), 19.12% (safe exploitation), 0.37% (planting adjustment), and 0% (strict control) in the CA. Thus, given the difference between Cd accumulation in rice and maize, adjustment of planting crops in contaminated farmlands can be applied to maximize the use of farmland resources. Graphical abstract: Image 1 Highlights: The contamination of Cd in rice, maize and soil caused by tin mining was investigated. Transfer ability of Cd in soil-rice system is stronger than soil-maize system. Soil CaO, TOC, pH and Mn are the controlling factors of Cd bioavailability. A suitable safe usage plan for local farmland was proposed by predictive models.